Β‐Blocker Therapy Prior to Admission for Acute Coronary Syndrome in Patients Without Heart Failure or Left Ventricular Dysfunction Improves In‐Hospital and 12‐Month Outcome: Results From the GULF‐RACE 2 (Gulf Registry of Acute Coronary Events‐2). Issue 12 (20th December 2017) - Abi Khalil, Charbel; AlHabib, Khalid F.; Singh, Rajvir; Asaad, Nidal; Alfaleh, Hussam; Alsheikh‐Ali, Alawi A.; Sulaiman, Kadhim; Alshamiri, Mostafa; Alshaer, Fayez; AlMahmeed, Wael; Al Suwaidi, Jassim
Abstract : Background: The prognostic impact of β‐blockers (BB) in acute coronary syndrome (ACS) patients without heart failure (HF) or left ventricular dysfunction is controversial, especially in the postreperfusion era. We sought to determine whether a BB therapy before admission for ACS has a favorable in‐hospital outcome in patients without HF, and whether they also reduce 12‐month mortality if still prescribed on discharge. Methods and Results: The GULF‐RACE 2 (Gulf Registry of Acute Coronary Events‐2) is a prospective multicenter study of ACS in 6 Middle Eastern countries. We studied in‐hospital cardiovascular events in patients hospitalized for ACS without HF in relation to BB on admission, and 1‐year mortality in relation to BB on discharge. Among the 7903 participants, 7407 did not have HF, of whom 5937 (80.15%) patients were on BB. Patients on BB tended to be older and have more comorbidities. However, they had a lower risk of in‐hospital mortality, mitral regurgitation, HF, cardiogenic shock, and ventricular tachycardia/ventricular fibrillation. Furthermore, 4208 patients were discharged alive and had an ejection fraction ≥40%. Among those, 84.1% had a BB prescription. At 12 months, they also had a reduced risk of mortality as compared with the non‐BB group. Even after correcting for confounding factors in 2 different models, in‐hospital and 12‐month mortality risk was still lower in the BB group. Conclusions: In this cohort of ACS, BB therapy before admission for ACS is associated with decreased in‐hospital mortality and major cardiovascular events, and 1‐year mortality in patients without HF or left ventricular dysfunction if still prescribed on discharge.